Development of a Play-Based Motor Learning Approach (A.MO.GIOCO) in Children with Bilateral Cerebral Palsy: Theoretical Framework and Intervention Methodology - Maria Foscan; Antonella Luparia; Francesca Molteni; Elisa Bianchi; Shari Gandelli; Emanuela Pagliano; Ermellina Fedrizzi (MDPI AG, 2024)
The early intervention of motor training based on specific tasks and parent empowerment represents the new paradigm for the rehabilitation of children with Cerebral Palsy (CP). However, most published studies address the problem of the effectiveness of rehabilitation intervention without describing the treatment methodology or briefly mentioning it. The purpose of the study is to illustrate the development of a play-based motor learning approach titled A.MO.GIOCO (Apprendimento MOtorio nel GIOCO) and its systematization. Fifteen children aged between 2 and 6 years with bilateral CP will be enrolled and treated for 6-8 weeks (48 h). Motor Teaching methods applied by senior therapists have been extensively described, starting from rehabilitation goals and proposed therapeutic play activities, tailored to the functional profile of each child. This child-friendly rehabilitative approach (A.MO.GIOCO) refers to the systemic cognitive model of learning and movement control and is implemented in the context of spontaneous play activities and in the therapist-child-family interaction. In this study the theoretical framework of the approach and the process followed by the therapists to transfer it into rehabilitative practice are highlighted. As a result, an operational guide has been created. Further studies will explore the efficacy of the proposed standardized approach.